(untitled) (Contemporary Journal of Social Science Review, 2024)
Child labor is an increasing issue that denies millions of children around the world their rights to a safe childhood, education, and health coverage. Having a spotlight on its consequences, causes, and potential remedies, this article examines numerous aspects of child labor. Child labor is when children are obligated to work at a young age, denying them of their education and happiness. The desire to support their family, poverty, and poverty are the main causes of child labor. Children who carry out hazardous endeavors including domestic work, mining, and agriculture in many developing countries suffer severe psychological and physical harm. Children are denied an opportunity of getting an education, which restricts their options in the future and perpetuating the poverty cycle. Also, they are subjected to dangerous conditions of employment which might lead to serious medical conditions, including as long hours, physical harm, and exploitation. If entire communities remain in poverty by the lack of sufficient education and skill development for future generations, child labor states to socioeconomic instability. Even though many nations have laws against them, it makes it difficult to follow them. Stronger regulations on labor should be enforced through governments and international organizations in order to promote better education for children, support families with few resources money-wise, and prosecute those who pressure young people to work.We must end child labor so that every child grows up in a safe environment, acquires an exceptional education, and leads a healthy life. By doing this, we can protect children’s rights while brightening their future.